The Influence Of Technology Based Marketing Strategies and Service Quality As Mediation Variables on Customer Loyalty - Kiky Tunjung Dewi (Jurnal sosial dan sains, 2022)
Marketing strategy is a form of directed planning in the marketing sector to obtain optimal results. Service quality is generally seen as a result of the overall service system that consumers receive. Loyalty as a condition in which customers have a positive attitude towards a brand The objectives of this study are: i) Knowing and analyzing technology-based marketing strategies that affect service quality. ii) Knowing and Analyzing Technology-Based Marketing Strategies affect Customer Loyalty. iii) Knowing and Analyzing Service Quality affects Customer Loyalty. iv) Knowing and analyzing the significant influence of Technology-Based Marketing Strategies on customer loyalty by mediating service quality in Bank Jatim. This type of research uses a quantitative research approach. The sample used was 44 respondents. The analysis used is Path Analysis. The results showed that: i) Technology-Based Marketing Strategy has a positive effect on the Service Quality of Bank Jatim Main Branch. ii) Marketing strategy has a positive effect on Customer Loyalty in Bank Jatim Main Branch. iii) Service Quality has a positive effect on Customer Loyalty in Bank Jatim Main Branch. iv) Technology-Based Marketing Strategy has a significant effect on Customer Loyalty by mediating Service Quality.